1983
DOI: 10.1111/j.1365-2141.1983.tb02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased T helper cells in the myelodysplastic syndromes

Abstract: The myelodysplastic syndromes (MDS) are disorders in which the abnormalities are thought to be confined to cells of the myeloid series. However, examination of peripheral blood from 56 patients with MDS showed that the majority had low lymphocyte counts. In a detailed study of 25 patients, using OKT3, OKT4 and OKT8 monoclonal antisera together with SRBC rosettes, it was shown that there is a consistent and significant reduction in peripheral blood T lymphocytes. This decrease was primarily confined to the OKT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Three (8%) of the reported 36 patients had chronic myelomonocytic leukemia. A decreased T-helper cell count and an immune dysfunction in myelodysplastic syndrome has also been confirmed by other authors [4,9]. In our patient we found a normal T-helper:T-suppressor cell ratio.…”
Section: Discussionsupporting
confidence: 76%
“…Three (8%) of the reported 36 patients had chronic myelomonocytic leukemia. A decreased T-helper cell count and an immune dysfunction in myelodysplastic syndrome has also been confirmed by other authors [4,9]. In our patient we found a normal T-helper:T-suppressor cell ratio.…”
Section: Discussionsupporting
confidence: 76%
“…Conversely, the defect of the immune system found in NHL also predisposes to MDS progression. 26,27 The third hypothesis is that co-existent MDS and NHL may be associated with upregulation of certain cytokines, such as interleukin (IL)-6 and vascular endothelial growth factor (VEGF). 28 Shimanoto et al 28 reported one patient with anaplastic large cell lymphoma who had trilineage myelodysplasia in the bone marrow that was associated with increased levels of IL-6 and VEGF at the time of diagnosis.…”
Section: Myelodysplastic Syndrome and T-cell Nhlmentioning
confidence: 99%
“…Various immunological abnormalities, including defective B and T cell immunity, hyper- or hypogammaglobulinemia, autoantibodies, and complement disturbances, have been reported in MDS [9] . Furthermore, a considerable reduction in natural killer cell activity has also been found in peripheral blood of MDS patients [15] . Lastly, ANA was positive and serum levels of IgA and IgM were elevated in our patient.…”
Section: Discussionmentioning
confidence: 98%